Hemorheology and Metabolism - Nemeth, Norbert (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This e-book version of the Special Issue "Hemorheology and Metabolites" has been dedicated to the novel findings and recent advances in hemorheology, presenting clinical or clinically oriented experimental research and review articles in the context of metabolites, metabolic alterations and blood macro- and micro-rheology.